Pengaruh Pengawasan Dan Disiplin Kerja Terhadap Produktivitas Karyawan PT. Kideco Jaya Agung Kecamatan Batu Sopang - Shalahuddin Shalahuddin; Danang Alfian Saputra; Dedy Darmawan (Islamic University of Kalimantan MAB Banjarmasin, 2020)
This study aims to determine the effect of monitoring variables (X1) and Work Discipline (X2) on employee productivity (Y) at the Planning Department of PT Kideco Jaya Agung, Batu Sopang District. The analytical tool used is multiple linear regression analysis that is processed with the help of SPSS. From the calculation results, the regression equation Y = 1.049 + 0.531X1 + 0.283X2 is obtained. The magnitude of the correlation coefficient (R) is 0.906. This shows that there is a solid relationship between supervisory variables (X1) and work discipline (X2) on employee productivity (Y), while the coefficient of determination R2 is 0.810. This shows that the supervisory variable (X1) and the work discipline variable (X2) have an effect of 81% on employee productivity (Y). In contrast, the remaining 19% is influenced by other variables not yet included in this study. From the results of the calculated F value of 82.156 > F table at 5% significance level with degrees of freedom (DB) = nk-1, that is 39-2-1 = 36, amounting to 3.26. This means that there is a joint effect between supervision (X1) and work discipline (X2) on employee productivity (Y). Furthermore, the t-test results showed that the supervision variable (X1) had a dominant effect on employee productivity (Y), obtained tcount> t-table (6.644> 2.028) and seen in the Coefficient Table that the supervision variable (X1) was 6.644 greater than the value of work discipline ( X2) of 2,585 (6,644> 2,585).Keywords: Employee Productivity, Supervision, Work Discipline